E-Booklet media can increase teenagers' knowledge about breast self-examination - Dahliana, Maya Dika; Agustina, Indah Fitri (Journal of Midwifery, 2023)
Breast cancer in women is the highest number of cancer cases in the world. Adolescents aged 10-21 years with breast cancer are often found at an advanced stage. This incident was caused by the low knowledge of teenagers about early detection of breast cancer with BSE. This research aims to determine the effectiveness of e-booklet media in increasing young women's knowledge regarding breast self-examination (BSE). This research is quantitative with a pre-experiment research design with a pre-test and post-test design without a control group design. The sampling technique in this research uses a probability sampling technique with a Simple Random Sampling approach. The sample consisted of 81 respondents who were high school students in DKI Jakarta. The research results showed an increase in the average knowledge score of young women after being given the E-Booklet media about BSE with a p-value < 0.001. Health service institutions and schools can utilize E-Booklet media during health education, especially for young women regarding BSE.